Role of Vitamin D in Prevention of Food Allergy in Infants - Giannetti, Arianna; Bernardini, Luca; Cangemi, Jessica; Gallucci, Marcella; Masetti, Riccardo; Ricci, Giampaolo (Frontiers in Pediatrics, 2020)
The prevalence of food allergy is increasing over the last decades. The role of vitamin D in the prevention of food allergy has been largely investigated. As it is well known the of calcitriol (the active form of vitamin D), has also effects on epithelial cells, T cells, B cells, macrophages and dendritic cells. Almost all cells of the adaptive immune system express the vitamin D receptor, making them also capable of being vitamin responsive. Specifically considering the potential role of vitamins in food allergy, vitamin D has been shown to affect several mechanisms that promote immunologic tolerance, including the T regulatory cell function and the induction of tolerogenic dendritic cells. The aim of our review is to evaluate the role of vitamin D in the prevention of food allergy in children. There are contradictory data on the association between the vitamin D deficiency and the development of food allergy. Some studies associate lower exposure to sunlight to food allergy, on the other hand, further research has found that higher levels of vitamin D could increase the likelihood of allergic sensitization and food allergy. Therefore, there is an urgent need for well planned randomized controlled trials on vitamin D supplementation, with particular regard to the prevention of food allergy. The role of vitamin D beyond bone and calcium metabolism not is fully understood.